2017
DOI: 10.1002/ptr.5823
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Activity of Gallic Acid In Vitro and In Vivo

Abstract: Gallic acid (GA) is a polyphenol natural compound found in many medicinal plant species, including pomegranate rind (Punica granatum L.), and has been shown to have antiinflammatory and antibacterial properties. Pomegranate rind is used to treat bacterial and fungal pathogens in Uyghur and other systems of traditional medicine, but, surprisingly, the effects of GA on antifungal activity have not yet been reported. In this study, we aimed to investigate the inhibitory effects of GA on fungal strains both in vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
74
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(91 citation statements)
references
References 27 publications
3
74
0
2
Order By: Relevance
“…Several authors proposed that gallic acid is also able to exert an antifungal activity against planktonic cultures and biofilm of C. albicans [12,13,20]. Moreover, Li et al [21] demonstrated that gallic acid inhibited the growth of different clinical isolates of Candida spp. and proposed that the fungicidal outcome was due to the impairment of biosynthesis of ergosterol, a fundamental component of the fungal membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors proposed that gallic acid is also able to exert an antifungal activity against planktonic cultures and biofilm of C. albicans [12,13,20]. Moreover, Li et al [21] demonstrated that gallic acid inhibited the growth of different clinical isolates of Candida spp. and proposed that the fungicidal outcome was due to the impairment of biosynthesis of ergosterol, a fundamental component of the fungal membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid is an antioxidant and it occurs as a free molecule or sometimes as part of a tannin molecule. It had been documented to possess several biological activities such as; antibacterial, anti-inflammatory, antifungal and anti-viral characteristics 11,13 . Gallic acid could be used in the treatment of albuminuria, diabetes and cancer 12 .…”
Section: Introductionmentioning
confidence: 99%
“…The hydrocinnamic acids found in the Crotalaria extract (caffeic acid and ferulic acid) are compounds belonging to the phenylpropanoid family, its structures award that they have biological properties such as antioxidant, antimicrobial [35], anticancer, anti-inflammatory and antithrombotic among others. Phenylpropanoid acids are precursors of C6-C1 aromatic compounds such as gallic acid, which induces apoptosis [36], and possesses antifungal properties [37] as well as caffeic acid [38].…”
Section: Discussionmentioning
confidence: 99%